A taxonomic review of the genus Physatocheila Fieber (Hemiptera: Heteroptera: Tingidae) from the Korean Peninsula, with description of a new species and a key to Korean Physatocheila species - Ji, Hankyul; Kim, Junggon; Jang, Geunho; Jung, Sunghoon (Zootaxa, 2023)
The genus Physatocheila Fieber is reviewed taxonomically from the Korean Peninsula, with a new species, Physatocheila koreaensis sp. nov. described. Morphological information such as the descriptions of adult specimens, male genitalia, and diagnoses are presented along with photographs. We also provide a key to the Korean Physatocheila species.